The Gendered Well-being Assessment: addressing trauma, complex needs & social determinants of health. - Ruprai, Denise; Pemberton, Simon; Summers, Richard (International Journal for Equity in Health, 2025)
Women's Centres in the UK provide crucial support to women with complex needs, who are often excluded from statutory services, frequently acting as a service of 'last resort'. A major challenge when working with this population is the lack of a holistic, validated, and gender-responsive assessment tool to measure needs comprehensively and systematically. This paper introduces the Gendered Well-being Assessment (GWA), a trauma-informed quality-of-life assessment designed for women with complex needs outside the criminal justice system. The GWA aims to support early intervention, enhance multi-agency collaboration, whilst offering a structured framework for case management. A comprehensive scoring algorithm combines contemporary research on accumulative complex trauma, complex needs, and toxic stress physiology with an overall aim to highlight unmet needs to avoid preventable harm and improve overall quality of life. The assessment takes account of the interconnectedness of needs, and across 5 key domains, and 12 sections create a comprehensive overview of the breadth and depth of needs. Unlike fragmented assessments, the GWA integrates multiple validated tools into a single framework, ensuring credibility within multi-agency partnerships. By recognising protective factors like self-efficacy and social support, the GWA moves beyond harm mitigation to promote resilience and flourishing. Its structured, algorithm-based approach informs personalised support plans, transforming service provision and policy. This innovative tool ensures that women's needs are addressed comprehensively and equitably within a broader social context.